2015
DOI: 10.1007/s10995-015-1712-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics Associated with Breastfeeding Initiation Among Canadian Inuit from the 2007–2008 Nunavut Inuit Child Health Survey

Abstract: We aimed to determine the prevalence of, and factors associated with, breastfeeding initiation in Canadian Inuit. We used data from the Nunavut Inuit Child Health Survey, a population-based, cross-sectional survey conducted in the Canadian territory of Nunavut. Inuit children aged 3-5 years in 2007 or 2008 were randomly selected for the survey. Select household, maternal, infant and community characteristics were collected from the child's primary caregiver and entered into logistic regression models as potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Children living in one of the sixteen selected communities were randomly sampled from lists provided by the community health centres and, as the sole source of health care in these communities, these lists were expected to be free of coverage errors. More information about the sampling strategy and the generation of sampling weights is provided elsewhere ( 4 , 21 ) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children living in one of the sixteen selected communities were randomly sampled from lists provided by the community health centres and, as the sole source of health care in these communities, these lists were expected to be free of coverage errors. More information about the sampling strategy and the generation of sampling weights is provided elsewhere ( 4 , 21 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Because our prior research has demonstrated food insecurity was not associated with beginning breast-feeding ( 21 ) , we restricted the present study to children who received some breast-feeding as infants. We excluded children who did not initiate breast-feeding because we were specifically interested in knowing, among those mothers who already began breast-feeding, whether food security played an instrumental role in their decision to continue breast-feeding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation